PENINGKATAN PENGETAHUAN DAN KETERAMPILAN GURU DALAM PENYUSUNAN LAPORAN PENELITIAN TINDAKAN KELAS (PTK) DI SMPN 2 SUNGGUMINASA GOWA - Abdullah; Sahril Nur; Mardiyanah Nasta; Murni Mahmud; Suci Pole Mappaita (Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Classroom Action Research (CAR) is an essential professional competency for teachers to continuously improve the quality of learning. However, teachers at SMPN 2 Sungguminasa Gowa face challenges in conceptual understanding and practical skills in developing proposals and reporting CAR results. This community service (PkM) activity aims to improve teachers' knowledge and skills in preparing and writing CAR reports. The method used is participatory training, which includes lectures, discussions, workshops, and intensive mentoring. This activity involved 25 teachers from various fields of study. The activity evaluation used pre- and post-test instruments to measure knowledge gains, and assessments of CAR proposal drafts and reports to measure skills. The activity results showed a significant increase in participants' knowledge, evidenced by a 78% increase in average post-test scores compared to the pre-test. Furthermore, 88% of participants successfully drafted systematic CAR proposals, and 40% were able to progress to drafting reports. This activity successfully provided practical solutions to partner problems and improved teachers' competency in conducting research in their classrooms.